2021
DOI: 10.1111/ijcp.14200
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of randomised, controlled trials on the effects of garlic supplementation on serum adiponectin and leptin levels

Abstract: Background: Our aim in this meta-analysis was to determine the effect of garlic supplementation on adiponectin and leptin serum levels.Method: A systematic search was conducted using PubMed, Scopus, ISI Web of Science and Cochrane Library for eligible trials up to November 2020. A fixed-effects model was used to pool calculated effect sizes.Results: Five trials were included in the overall analysis. Our analysis showed that garlic supplementation did not significantly affect adiponectin (Hedges's: 0.20; 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The previous documents have revealed that garlic may affect adipokines through antioxidant properties. For example, garlic increases the nitric oxide bioavailability via advancing the cellular antioxidant capacity by providing cellular thiol antioxidants like cysteine and diminished glutathione, maintaining the functionally appropriate concentration of tetrahydrobiopterin and controlling oxidative inactivation of tetrahydrobiopterin [ 51 52 ]. Thus, according to the mentioned mechanisms, the consumption of soluble fiber can be suggested to manage leptin levels and resistance among overweight or obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The previous documents have revealed that garlic may affect adipokines through antioxidant properties. For example, garlic increases the nitric oxide bioavailability via advancing the cellular antioxidant capacity by providing cellular thiol antioxidants like cysteine and diminished glutathione, maintaining the functionally appropriate concentration of tetrahydrobiopterin and controlling oxidative inactivation of tetrahydrobiopterin [ 51 52 ]. Thus, according to the mentioned mechanisms, the consumption of soluble fiber can be suggested to manage leptin levels and resistance among overweight or obese subjects.…”
Section: Discussionmentioning
confidence: 99%